2021
DOI: 10.1002/1878-0261.12998
|View full text |Cite
|
Sign up to set email alerts
|

Cyr61 from adipose‐derived stem cells promotes colorectal cancer metastasis and vasculogenic mimicry formation via integrin αVβ5

Abstract: Cyr61 from adipose-derived stem cells promotes colorectal cancer metastasis and vasculogenic mimicry formation via integrin α V β 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In addition, Habel et al [56] found that knockdown of CYR61 expression in osteosarcoma downregulates various angiogenic proteins, including VEGF-A, leading to suppression of tumor angiogenesis. More recently, signal transducer and activator of transcription 3 (STAT3), a member of the STAT family that plays an important role in cell proliferation, differentiation, apoptosis, tumorigenesis, and angiogenesis [57], was detected in exosomes secreted from colorectal cancer cells; these exosomes have been shown to induce adipose-derived stem cells to upregulate CYR61 expression, yielding the formation by colorectal cancer cells of vasculature-mimicking tissue via a VEGF-independent process [58].…”
Section: The Possible Existence Of Vegf-independent and Vegfr2-depend...mentioning
confidence: 99%
“…In addition, Habel et al [56] found that knockdown of CYR61 expression in osteosarcoma downregulates various angiogenic proteins, including VEGF-A, leading to suppression of tumor angiogenesis. More recently, signal transducer and activator of transcription 3 (STAT3), a member of the STAT family that plays an important role in cell proliferation, differentiation, apoptosis, tumorigenesis, and angiogenesis [57], was detected in exosomes secreted from colorectal cancer cells; these exosomes have been shown to induce adipose-derived stem cells to upregulate CYR61 expression, yielding the formation by colorectal cancer cells of vasculature-mimicking tissue via a VEGF-independent process [58].…”
Section: The Possible Existence Of Vegf-independent and Vegfr2-depend...mentioning
confidence: 99%
“…This results in an increased cell migration and invasion, as well as CRC metastasis. Inhibition of the STAT3 signaling could decrease the expression of Snail1, Twist1, and MMP2 (40,41). Here, TRIM6 knockdown decreased the expression of Snail1, Twist1, and MMP2 (Figure 1), which may be due to the decreased phosphorylation of STAT3 through inhibiting the ubiquitination of SOCS2.…”
Section: Discussionmentioning
confidence: 89%
“…28 Malignant tumor cells can form tubular neovascularization by VM to promote cancer invasion. 29,30 Epithelial-mesenchymal transition seems to be connected with the VM process of tumor migration in prior research. 31 Emerging studies have unveiled that F. nucleatum affected METTL3 to modulate CRC occurrence and aggressiveness.…”
Section: Introductionmentioning
confidence: 93%
“…Methyltransferase‐like 3 could promote tumor cell invasion and migration by accelerating EMT formation 28 . Malignant tumor cells can form tubular neovascularization by VM to promote cancer invasion 29,30 . Epithelial–mesenchymal transition seems to be connected with the VM process of tumor migration in prior research 31 .…”
Section: Introductionmentioning
confidence: 99%